2017
DOI: 10.1371/journal.pone.0184970
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin increases the migration of human fibroblasts and affects the endothelial cell network formation: A possible role for cancer-associated fibroblasts in breast cancer progression

Abstract: In our previous studies we showed that in breast cancer podoplanin-positive cancer-associated fibroblasts correlated positively with tumor size, grade of malignancy, lymph node metastasis, lymphovascular invasion and poor patients’ outcome. Therefore, the present study was undertaken to assess if podoplanin expressed by fibroblasts can affect malignancy-associated properties of breast cancer cells. Human fibroblastic cell lines (MSU1.1 and Hs 578Bst) overexpressing podoplanin and control fibroblasts were co-cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 49 publications
1
38
1
Order By: Relevance
“…MT1-2 + was mostly limited to CD45 + and sub-epicardial cells at d5. Consistently, SPRING analysis showed that the IR cluster evolved from high expression of Mt1-2 and stromal and fibroblast genes (Gsn [Witke et al, 1995], Pdpn [Suchanski et al, 2017], Angptl4) on d1 to low expression of Mt1-2 accompanied by Myofb markers (Fn1, Acta2, Cthrc1) on d3 ( Figure 4F), suggesting that IR cells rapidly transition to Myofb, in contrast to a previous report suggesting the appearance of Myofb not earlier than d7 post-MI (Farbehi et al, 2019).…”
Section: Dynamics Of Stromal Populations Involved In Scar Formationsupporting
confidence: 81%
“…MT1-2 + was mostly limited to CD45 + and sub-epicardial cells at d5. Consistently, SPRING analysis showed that the IR cluster evolved from high expression of Mt1-2 and stromal and fibroblast genes (Gsn [Witke et al, 1995], Pdpn [Suchanski et al, 2017], Angptl4) on d1 to low expression of Mt1-2 accompanied by Myofb markers (Fn1, Acta2, Cthrc1) on d3 ( Figure 4F), suggesting that IR cells rapidly transition to Myofb, in contrast to a previous report suggesting the appearance of Myofb not earlier than d7 post-MI (Farbehi et al, 2019).…”
Section: Dynamics Of Stromal Populations Involved In Scar Formationsupporting
confidence: 81%
“…For generation of the GAL3ST1-expressing vector, the human GAL3ST1 cDNA was amplified by PCR from the MCF7 cDNA library using the primers presented in Additional file 1 : Table S1. The resulting insert was cloned into a pRRL-CMV-IRES-PURO vector as described previously [ 18 ] and named here as pRRL-CMV-GAL3ST1-IRES-PURO. For lentivirus production, packaging LentiX 293 T cells were co-transfected at 50–60% confluence with 20 μg of expression or control vector, 10 μg pMDL-g/p-RRE, 5 μg pRSV-REV and 5 μg pMk-VSVG (kindly provided by Dr D. Trono, École Polytechnique Fédérale de Lausanne, Switzerland) using polyethylenimine (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…In mesenchymal stromal cells, it has been shown that podoplanin expression is required for Rac1-dependent migration (30). Furthermore, podoplanin drives cell migration of CAFs (31) and cancer cells (32,33), and as such plays a role in several stages of the metastasis process (1). Podoplanin is expressed at the invasive front of tumours (34), and more specifically recruited to the adhesion ring of invadopodia where it localizes in lipid rafts (35).…”
Section: Introductionmentioning
confidence: 99%